2013
DOI: 10.3109/15419061.2013.775257
|View full text |Cite
|
Sign up to set email alerts
|

Role of Transcription Factors in the Pathogenesis of Asthma and COPD

Abstract: Infl ammation is a central feature of asthma and chronic obstructive pulmonary disease (COPD). Despite recent advances in the knowledge of the pathogenesis of asthma and COPD, much more research on the molecular mechanisms of asthma and COPD are needed to aid the logical development of new therapies for these common and important diseases, particularly in COPD where no effective treatments currently exist. In the future the role of the activation/repression of different transcription factors and the genetic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 208 publications
(236 reference statements)
2
52
0
Order By: Relevance
“…Transcriptional regulators of inflammatory genes including those related to cytokines, adhesion molecules, enzymes and receptors, is part of the molecular signaling that drives the development and progression of lung pathologies such as asthma and COPD [45, 46]. Therefore, not surprisingly, we predicted increased activation of TFs with well-known roles in emphysema development, such as NF-κB [10, 45, 4752], but we also revealed TFs with less described or unknown roles in the etiology of emphysema.…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptional regulators of inflammatory genes including those related to cytokines, adhesion molecules, enzymes and receptors, is part of the molecular signaling that drives the development and progression of lung pathologies such as asthma and COPD [45, 46]. Therefore, not surprisingly, we predicted increased activation of TFs with well-known roles in emphysema development, such as NF-κB [10, 45, 4752], but we also revealed TFs with less described or unknown roles in the etiology of emphysema.…”
Section: Discussionmentioning
confidence: 99%
“…55 Bacterial lysates are recommended in the treatment of COPD, which is characterized by increased transcription of proinflammatory factors such as cytokines, chemokines, growth factors, and enzymes that results in inflammation and tissue damage. 56 It was recently demonstrated that peripheral blood mononuclear cells from patients with COPD exposed to bacterial lysates in vitro released more IL-10. 32 The increase in immunoregulatory IL-10 secretion could regulate the production of proinflammatory mediators, thereby providing a rationale for the use of bacterial lysates to prevent acute exacerbation in patients with COPD.…”
Section: Clinical Outcomes Of Bacterial Lysate Therapy In Adult Respimentioning
confidence: 99%
“…ASM growth is promoted by growth factors, chemokines, and inflammatory cytokines and involves activation of multiple intracellular signaling cascades that ultimately induce several key transcription factors involved in regulating cell proliferation (9). Using luciferase reporter assays, we investigated activation of 10 (CRE, STAT3, E2F, C/EBP, SRE, Myc, NF-B, NFAT, Smad, and AP-1) different transcription factors to gain further insight into the mechanisms mediating the antimitogenic effects of TAS2R agonists.…”
Section: Tas2r Agonist-mediated Antimitogenic Effect Does Not Involvementioning
confidence: 99%